2017
DOI: 10.5897/ajar2016.11865
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional diagnosis of sugarcane varieties in a Yellow Oxisol during three agricultural seasons

Abstract: Leaf analysis is one of the main methods used for the evaluation of nutritional requirements in sugarcane culture, contributing to a better management of fertilizers. This study aimed to evaluate the nutritional status of sugarcane varieties by quantifying the leaf content of macro and micronutrients of the +3 leaf. The varieties RB92579, RB867515, VAT90-212 and SP813250 were evaluated in a Yellow Oxisol at Fazenda Jequiá, Anadia, Alagoas (AL) state, during plant-cane, first and second regrowth cycles. The des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…In this context, studies that evaluate the nutritional demand of sugarcane varieties are fundamental, since fertilization constitutes a significant part of the production costs of the sugarcane industry (Silva et al, 2017b), however, studies that identify nutrient requirements have not been carried out frequently, and the information available mostly refers to varieties that are no longer planted (Oliveira et al, 2010). The results of these studies have shown that cultivars may present variations in nutrient extraction (Oliveira et al, 2010;Calheiros et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, studies that evaluate the nutritional demand of sugarcane varieties are fundamental, since fertilization constitutes a significant part of the production costs of the sugarcane industry (Silva et al, 2017b), however, studies that identify nutrient requirements have not been carried out frequently, and the information available mostly refers to varieties that are no longer planted (Oliveira et al, 2010). The results of these studies have shown that cultivars may present variations in nutrient extraction (Oliveira et al, 2010;Calheiros et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The climate is tropical rainy with dry summers, according to Koppen classification. The average annual rainfall is 1,200 mm and the average temperature is 29 ºC (Silva et al, 2017a). The soil of the experimental area was classified as a Latossolo Amarelo (Embrapa, 2013).…”
Section: Description Of the Experimental Areamentioning
confidence: 99%
“…The varieties were chosen because of their high yield and industrial quality (Silva, 2017a(Silva, , 2017b, in addition to the high representativeness. The sum of their cultivated areas was more than 50% of the area planted with sugarcane in the Northeast of Brazil, one year prior to the installation of the experiment.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations